Analisis Konsep Pendidikan Karakter Imam Al-Ghazali (Bidayatul Hidayah) dan Implikasinya bagi Pendidikan Karakter di Indonesia - Yayuk Ismawa; M. Fatchul Ulum (Journal of Transdisciplinary Studies in Religion and Education, 2025)
This research is motivated by the increasingly fading moral education in modern society, which has led to many deviations in values. Efforts to purify it can be carried out by referring to Islamic teachings, especially the thoughts of Imam Al-Ghazali. The focus of this research is (1) the values ​​of character education in the book Bidayatul Hidayah and (2) the concept of character education according to Imam Al-Ghazali and its relevance to character education in Indonesia. The method used is a literature study with the primary source of the book Bidayatul Hidayah and secondary sources in the form of related literature. The results of the study indicate that character education, according to Imam Al-Ghazali, emphasizes the formation of both physical and spiritual personality so that humans obey God. This concept is relevant to character education in Indonesia because it covers aspects of relationships with God, oneself, and society comprehensively.